The effect of multiple lightning impulse on the electrical characteristic of opto-isolator as lightning protective devices - Sidik @ Mat Sidek, Ahmad (2008)
The behavior and performance of surge protective devices such as optoisolator under the application of multiple lightning voltage impulse are different from the single lightning voltage impulse test. Since opto-isolator is becoming the most common, economical and reliable device for low voltage systems surge protection, a precise method of testing has to be adopted based on natural characteristics of lightning. This is to ensure that the performance and capability of the device is precisely determined. In this work, laboratory studies are carried out on opto-isolator subjected to 1/1000µs, 1kV multiple voltage impulses by using the Multiple Impulse Generator, MIGe. The electrical responses such as collector emitter breakdown voltage, V(BR)CEO; emitter collector breakdown voltage, V(BR)ECO and collector base breakdown voltage, V(BR)CBO are then being analyzed to determine the effect to the opto-isolator characteristic. Results from the laboratory works shows that the multiple lightning voltage impulse has significant effects on the collector emitter breakdown voltage V(BR)CEO and emitter collector breakdown voltage V(BR)ECO characteristics of the opto-isolator and no significant was observed for parameter of collector base breakdown voltage, V(BR)CBO.